Effectiveness of Sensory Stimulations in Improving Balance in Patients suffering from Peripheral Diabetic Neuropathy - Dr. Aishwarya Rai,; Shaswat Kumar Chandan,; Supriyo Sarkar,; Yogakshi Banga, (The Bioscan, 2026)
Objectives: There is little study explicitly examining the efficacy of multimodal sensory stimulation Patients suffering from Peripheral Diabetic Neuropathy, despite its prevalence and associated effects on balance. In order to improve balance, this study assesses how sensory stimulations affect sensation. Methods: An experimental study design was designed and 38 participants were gathered for the investigation. The experimental group, to which the people were randomly assigned, got mixed sensory stimulation, while the control group was given conventional care. Tests such as Berg Balance Scale were used to evaluate balance outcomes, while the Michigan Neuropathy Screening Instrument was used to evaluate sensory complaints. These evaluations were carried out both before and after the intervention. Results: Group A and Group B's post-BBS and MNSI scores were compared using a t-test value of 0.006808 and 0.01 correspondingly. Group A and Group B's post-BBS and MNSI scores differ significantly, as indicated by these figures (0.006808, 0.01). Therefore, it can be concluded that, in comparison to Group B, the combined sensory stimulation therapies carried out in Group A had a favorable effect on both balance (BBS scores) and neuropathy (MNSI scores). Conclusion: Therefore, based on the study's findings, we can say that multimodal sensory stimulation therapies are useful ways to help people with peripheral diabetic neuropathy become more balanced. By enhancing sensory input, proprioception, and balance control, these therapies can increase functional mobility and reduce the risk of falls. understanding